Hemorrhagic fever viruses: Pathogenesis, therapeutics, and emerging and re-emerging potential - Flórez-Álvarez, Lizdany; de Souza, Edmarcia Elisa; Botosso, Viviane Fongaro; de Oliveira, Danielle Bruna Leal; Ho, Paulo Lee; Taborda, Carlos Pelleschi; Palmisano, Giuseppe; Capurro, Margareth Lara; Pinho, João Renato Rebello; Ferreira, Helena Lage; Minoprio, Paola; Arruda, Eurico; et al. (Frontiers in Microbiology, 2022)
Hemorrhagic fever viruses (HFVs) pose a threat to global public health owing to the emergence and re-emergence of highly fatal diseases. Viral hemorrhagic fevers (VHFs) caused by these viruses are mostly characterized by an acute febrile syndrome with coagulation abnormalities and generalized hemorrhage that may lead to life-threatening organ dysfunction. Currently, the events underlying the viral pathogenicity associated with multiple organ dysfunction syndrome still underexplored. In this minireview, we address the current knowledge of the mechanisms underlying VHFs pathogenesis and discuss the available development of preventive and therapeutic options to treat these infections. Furthermore, we discuss the potential of HFVs to cause worldwide emergencies along with factors that favor their spread beyond their original niches.